ANALISIS KELAYAKAN USAHA PEMBUATAN PAKAN TERNAK KOMPLIT DENGAN MEKANISASI SKALA KELOMPOK DI KABUPATEN SUBANG - Ferdi Fathurohman; Ridwan Baharta (JURNAL AGRIBISNIS TERPADU, 2020)
Based on the forage potential of livestock in Subang Regency in groups with forage potential livestock feed is facilitated by integrated animal feed processing equipment so that the economic value of anima feed at the farmer level will be more than complete animal feed.Complete animal feed can be an agricultural business opportunity to provide added value from animal feed. Therefore it is necessary to conduct a business feasibility analysis in terms of the financial aspects of the business of complete animal feed, whose production uses mechanization. This study aims to determine the financial analysis of the complete animal feed business, which uses mechanization with a scale of livestock groups in Subang Regency. This research was conducted in Subang Regency from January to March 2019. The research method used in this study was by directly making complete animal feed products using mechanization tools and calculating the financial aspects of the business. Break Even Point is 1200 packs, Net Present Value is positive or greater than zero, Internal Rate of Return is greater than MARR value and actual interest rate, Production value is more than Rp. 100,000,000 or net value of more than Rp. 60,000,000, - / group / year, compared with the value of basic products with a production value of Rp. 22,000,000, - or the net income value is only Rp. 11,000,000 / year. The 2.5 year payback period does not exceed the planned business period. B/C Ratio 1.3 whose value is greater than 1. So that from a financial standpoint a complete animal feed business that uses tools or mechanization is feasible to run. Sensitivity analysis carried out with the influence of inflation approach of 8.79% does not affect the complete animal feed business.